SOFT POWER THROUGH LANGUAGE: HOW ENGLISH SHAPES GLOBAL DIPLOMACY (European Journal of Interdisciplinary Research and Development, 2025)
This article explores the role of the English language as a strategic instrument of soft power in international diplomacy. It examines how English, as the dominant global lingua franca, enables countries to extend influence through education, media, and cultural diplomacy rather than through force or economic pressure. Drawing on theories of soft power, real-world case studies, and the work of institutions like the British Council, Fulbright Program, and U.S. Department of State, the article analyzes how English is used to shape global narratives, build international alliances, and promote national interests. It also addresses the ethical and cultural implications of linguistic dominance, including the marginalization of non-English-speaking voices. The study contributes to discussions in international relations, sociolinguistics, and cultural studies, offering insights into how language functions not only as a means of communication but as a subtle and powerful diplomatic tool.